Peran Aplikasi Seluler dalam Mengubah Paradigma Bisnis dan Layanan Konsumen - ., Diva Andzani; ., Irwansyah (CV. ITTC INDONESIA, 2023)
This writing aims to investigate the significant role of mobile applications in transforming the paradigm of business and consumer services in the context of the digital era. The primary focus is on the impact of mobile applications on the business strategies of companies and the consumer experience. The research reveals how the adoption of mobile applications can enhance the operational efficiency of companies, accelerate responses to market changes, and establish more direct interactions with consumers. The study's findings indicate that consumers experience smoother interactions, improved service accessibility, and the formation of stronger loyalty through mobile applications. The conclusion of this study underscores the importance of a deep understanding of the crucial role of mobile applications in shaping the future of responsive, efficient, and innovative business and consumer services.